Manajemen Mutu Program Diniyah Pada Pondok Pesantren MuhammadIyah Lamongan - Ali Hamdi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2019)
The main problem in this research is how the quality management developed at the madrasa diniyah is boarded in the muhammdiyah lamongan pesantren. In accordance with these problems, the objectives of this study are (1) how is the quality planning (2) how is the quality program implemented (3) How is quality monitoring and evaluation (4) how is the quality improvement action carried out by boarding muhammadyah lamongan boarding school. The research method uses qualitative methods, with the reason that the questions are open so that researchers can be flexible and can develop questions, because researchers want to describe and analyze the implementation of quality management in Islamic boarding schools in Muhammadiyah dilamongan, Madrasah diniyah Islamic boarding schools in Muhammadiyah Lamongan, the results of the study show that there are several diniyah muhammdiyah Islamic boarding school program in lamongan has developed quality management starting from planning, implementation of monitoring and evaluation as well as follow-up of quality improvement which is very synergic between madrasa and Islamic boarding school so that the existence of madrasa diniyah and pondok pesantren continues to develop. Recommendations, this study recommends that madrash diniyah and lamuh muhammadyah Islamic boarding schools should continue to be quality teamwork in improving quality with structured roles and responsibilities, and become models that can be used as alternative concepts for quality management of madrasa diniyah. Key words: Quality Management , Madrasah diniyah, and Islamic Boarding School Muhammadiyah dilamongan